Sarriá 82: what Art Football lacked - Sousa Junior, José Dantas de (2020)
We seek here to analyze the book Sarriá 82: O que missing ao Futebol Arte, by journalist Renato Zanata along with game collector Gustavo Roman. We aim to unmask some existing myths in the history of Brazilian sport, specifically Football, taking advantage of the work analyzed here. This sport, the greatest passion of the Brazilian people, the most practiced in the whole world, not only in this century, but since the last century. We can say that at the end of the 50's, until the beginning of the 80's, Brazil had the best players in the world, which brought to the Brazilian a superiority complex and of "already won" in the events he would dispute. Consequently, with some defeats throughout history, villains, responsible and "scapegoats" emerged. Examples, Barbosa in 1950 and Toninho Cerezo in 1982. Much easier to blame a defeat on a citizen who is not handsome, dark in color and mustache, instead of blaming a coach with another profile, more sympathetic and charismatic , but who commanded the team the way he wanted, without listening to anyone and refusing a draw out of pure pride, not only his own but also representing the feeling of a people, or most of them.